Joshua Dread - Bacon, Lee. (New York : Yearling, an imprint of Random House Children's Books, a division of Random House, Inc., 2013)
Besides being bullied, Joshua faces one more obstacle in middle school, trying to hide his identity as the son of supervillains, the Dread Duo.
School Library Journal, February 2013.
Horn Book, November 2012.
Choice, April 2013.
Kirkus Review, August 2012.
Library Media Connection, May 2013.
Publishers Weekly Annex, October 2012.
Keywords: Supervillains -- Juvenile fiction; Superheroes -- Juvenile fiction; Identity (Philosophical concept) -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Supervillains -- Fiction; Superheroes -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Identity -- Fiction